Epidemiology and management practices for childhood-onset systemic lupus erythematosus patients: a survey in Latin America - Ferreira, Juliana C. O. A.; Trindade, Vitor C.; Espada, Graciela; Morel, Zoilo; Bonfá, Eloisa; Magalhães, Claudia S. [UNESP]; Silva, Clovis Artur (Springer Nature, 2018)
To assess epidemiology and management practices of Latin America Pediatric Rheumatologists (LAPR) about childhood-onset systemic lupus erythematosus (cSLE). A cross-sectional study was performed in 288 LAPR PANLAR members based on online survey about cSLE practices. The response rate of web-based survey by LAPR was 170/288(59%) and the majority worked in university hospitals (63%). The ACR and/or SLICC classification criteria (99%) and disease activity tools (97%) were almost universally used by LAPR, whereas damage index (70%) and CHAQ (58%) instruments were less frequently used. Laboratory exams, diagnostic imaging, and biopsies were generally available (> 75%), however low availability for densitometry (66%). Drug access was excellent for the most common prescribed medications (> 75%), except for belimumab (11%). Emerging mosquito-borne diseases were also reported: dengue (20%), chikungunya (11%), and Zika (8%). Groups were further divided in two, according to the median number of cSLE patients followed by LAPR in the last year: groups A and B (≥ 25 and < 25, respectively). Frequencies of condom in combination with other contraceptive methods were significantly higher in group A than B (p = 0.01). The frequencies of reported pregnancy (p < 0.001) and non-adherence to therapy were significantly higher in group A (p = 0.023). Alcohol intake (p = 0.004) and illicit drug use (p = 0.007) were also reported more frequently by LAPR of group A in at least one cSLE patient. This first large web-based survey demonstrated an overall excellent access for diagnosis and therapy by LAPR, probably related to their high rate of practices in tertiary care of university hospitals. Adherence to therapy, pregnancy, and substance abuse was identified as major challenges in this population, particularly in larger centers.
Keywords: Adolescent; Childhood-onset systemic lupus erythematosus; Children; Epidemiology; Latin America; Survey